2017
DOI: 10.1002/nme.5520
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of pressure distribution to arbitrary geometry with boundary condition represented by polygons in particle method

Abstract: The boundary condition represented by polygons in the moving particle semi-implicit method can accurately represent geometries and treat complex geometry with high efficiency. However, inaccurate wall contribution to the Poisson's equation leads to drastic numerical oscillation. To address this issue, in this research, we analyzed the problems of the Poisson's equation used in the boundary condition represented by polygons. The new Poisson's equation is proposed based on the improved source term (Tanaka and Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…To solve this problem, it is necessary to further investigate the particle arrangement and related boundary conditions for arbitrary complex shapes in future research. In this regard, several recent studies [45,46] have been reported by researchers employing the particle method. Second, as shown in Figure 29, when the wave elevation time series is compared at a 1 m point in front of the RM3 structure depending on the presence or absence of RM3, a WEC structure, it is observed that the elevation of the incoming waves decreases by approximately 3.3% owing to the waves diffracted by the WEC structure.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…To solve this problem, it is necessary to further investigate the particle arrangement and related boundary conditions for arbitrary complex shapes in future research. In this regard, several recent studies [45,46] have been reported by researchers employing the particle method. Second, as shown in Figure 29, when the wave elevation time series is compared at a 1 m point in front of the RM3 structure depending on the presence or absence of RM3, a WEC structure, it is observed that the elevation of the incoming waves decreases by approximately 3.3% owing to the waves diffracted by the WEC structure.…”
Section: Simulation Resultsmentioning
confidence: 99%